STUDIES ON EFFECT OF SOAKING TIME, TEMPERATURE AND pH ON THE YIELD OF SORGHUM STARCH (SORGHUM BICOLOR) VARIETY PVK-801 - V. V. BANSODE,; D. K. KAWADKAR,; D. N. KSHIRSAGAR,; V. D. PAWAR,; A. W. MORE, (The Bioscan, 2014)
The suitability of sorghum as a source of starch was investigated. The effects of soaking time, temperature and pH on the yield of starch were optimized and its functional and rheological properties were studied. The sorghum grain flour contained 74.50% starch. Soaking time of 20 h, temperature of 50ºC and pH of 4.5 resulted in maximum yield (75.5%) of starch.The solubility and swelling of sorghum starch were maximum at 90ºC viz. 19.25% and 18.10% respectively. The starch at 10% level yielded an apparent viscosity of 1998.50 Cps at 90ºC using shear rate of 4.51 S-1.